Intrapatellar tendon lipoma with chondro-osseous differentiation: detection of HMGA2-LPP fusion gene transcript. Issue 4 (27th March 2006) - Matsui, Y; Hasegawa, T; Kubo, T; Goto, T; Yukata, K; Endo, K; Bando, Y; Yasui, N
Abstract : A 54 year old man developed an unusual lipoma in the patellar tendon, consisting of a fibro-adipose component and a chondro-osseous component. The fibro-adipose component contained mature adipocytes, lipoblasts, and fibroblasts; the chondro-osseous component showed typical endochondral bone formation. Molecular analysis showed that the identical HMGA2-LPP fusion transcript—characteristic of lipoma, parosteal lipoma, and pulmonary chondroid hamartoma—was detectable in the both components.